Distinct microbiome composition and reduced interactions in patients with pancreatic cancer - Kim, Bomi; Oh, Sujin; Yang, Soomin; Ahn, Jinwoo; Jung, Kwangrok; Lee, Jong-Chan; Hwang, Jin-Hyeok; Shin, Cheol Min; Lee, Hyo-Jung; Lee, Hye Seung; Kim, Jaihwan; Park, Kyoung Un (Frontiers in Microbiology, 2025)
IntroductionThe results of microbiome composition in patients with malignancy have been inconsistent across studies and are affected by various factors. This study aimed to identify microbiome composition of saliva, feces, and blood in patients with pancreatic cancer.ResultsOverall, 31 patients with pancreatic cancer and 24 healthy controls were sex- and age-matched. Microbiome analysis of saliva, fecal, and blood samples was conducted using 16S rRNA amplicon sequencing. Baseline characteristics were comparable between patients and controls. Saliva showed insignificant difference in alpha diversity (p = 0.42), whereas feces and blood exhibited a significant difference in Shannon’s index (feces: 6.19 vs. 6.52, p = 0.013; blood: 8.00 vs. 7.49, p < 0.001) between patients and controls. Beta diversity analysis revealed significant differences between saliva, fecal, and blood samples (p = 0.014, 0.001, and 0.001, respectively). Distinct microbiome compositions were identified in patients, with higher abundance of Lactobacillus, Enterobacter, and Prevotella in saliva, fecal, and blood samples, respectively. Based on microbial network analysis, patients with pancreatic cancer showed lower clustering coefficient (71% vs. 99%) and higher average path length (1.67 vs. 0.68) than healthy controls, suggesting a more compact network and stronger microbial interactions in healthy controls.ConclusionThis study identified a distinctive microbiome in patients with pancreatic cancer, indicating the presence of Lactobacillus, Enterobacter, and Prevotella. A less condensed and robust microbial interaction network was observed in blood samples of patients with pancreatic cancer. These findings provide a basis for research on the connection between the microbiome and pancreatic cancer.